2012
DOI: 10.1111/j.1365-2095.2011.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutriphysiological and cytological responses of juvenile channel catfish (Ictalurus punctatus) to dietary oxidized fish oil

Abstract: An 86-day growth trial was conducted to investigate the effect of dietary oxidized fish oil on the growth and cytopathology of juvenile channel catfish (Ictalurus punctatus). Four diets containing 0 g kg À1 (control: fresh fish oil), 30 g kg À1 (low-oxidized oil group), 60 g kg À1 (medium-oxidized oil group) and 90 g kg À1 (high-oxidized oil group) graded oxidized oil levels with the same dietary lipid level (90 g kg À1 diet) were evaluated. The results show that the specific growth rate decreased with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…In addition, fish regulate their feed intake depending on their energy requirement (Kaushik and Luquet, 1984). Similar finding was also observed in other fishes after exposure to dietary toxins (MCs, aflatoxin B 1 and oxidized fish oil), which the fishes may increase their feed intake in relation to "energy requirement" for maintaining their physiological requirement or combating the oxidative stress induced by toxins Dong et al, 2009Dong et al, , 2012Huang et al, 2011).…”
Section: Effect Of Dietary Cyanobacteria On the Growth Performance Ofsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, fish regulate their feed intake depending on their energy requirement (Kaushik and Luquet, 1984). Similar finding was also observed in other fishes after exposure to dietary toxins (MCs, aflatoxin B 1 and oxidized fish oil), which the fishes may increase their feed intake in relation to "energy requirement" for maintaining their physiological requirement or combating the oxidative stress induced by toxins Dong et al, 2009Dong et al, , 2012Huang et al, 2011).…”
Section: Effect Of Dietary Cyanobacteria On the Growth Performance Ofsupporting
confidence: 61%
“…Similar result was also observed in hybrid tilapia after exposure to highcyanobacteria diet (Dong et al, 2009). This higher FR in yellow catfish fed with the HCD could be due to the Hormesis (a biphasic doseeresponse with a low dose stimulation or beneficial effect and a high dose inhibitory or toxic effect) (Calabrese, 1999) and dietary toxins (MCs, aflatoxin B 1 and oxidized fish oil) are sometimes known to have stimulant properties and then resulted in higher FR in our previous study Dong et al, 2009Dong et al, , 2012Huang et al, 2011). In addition, fish regulate their feed intake depending on their energy requirement (Kaushik and Luquet, 1984).…”
Section: Effect Of Dietary Cyanobacteria On the Growth Performance Ofmentioning
confidence: 99%
“…However, only a few investigations analysed the effects of dietary oxidized lipids on affected tissues at the cellular and subcellular level. Dong et al () confirmed that highly oxidized fish lipid led to cellular injury in the liver, kidney and muscle tissues of channel catfish. Likewise, Laohabanjong et al () found that oxidized lipids in fish meal caused degenerative changes in the hepatopancreatic tubules of black tiger shrimp.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, statistically significant lower body weight gains, FEs and HPIs were observed in crabs fed on diets containing OFO, which was quite consistent with reports in whiteleg shrimp (Yang et al, ). When fed on diets with OFO, some fish, such as channel catfish ( Ictalurus punctatus ) and black sea bream ( Acanthopagrus schlegeli ), also showed lower survival rates (Dong et al, ; Peng et al, ). Similarly, in a previous study in which mitten crabs were fed on diets with up to 6% OFO, a lower survival was observed (Wang, Li, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…. . lack of information is due to the fact that most of the studies dealing with dietary oxidized lipids have been conducted using inert diets (Mourente et al 2002;Fontagn e et al 2006;Zambrano & Landines 2011;Dong et al 2012). However, sufficient levels of VE can be accumulated and maintained in Artemia metanauplii, making this live food a delivery system useful for studying dietary requirements as well as the antioxidant effects of VE in marine fish (Huo et al 1996).…”
Section: Figurementioning
confidence: 98%